Comparação da bioimpedância frente ao padrão ouro para composição corporal em idosas - Ayub, Pollyanna (2018)
Objective: to compare distinct bioimpedances (BIAs) in front of the gold standard for body composition in elderly women, verifying the existence of a correlation between the methods and the necessity or not of using a previous protocol of hydration. Methods: a cross-sectional, descriptive and comparative study with 83 elderly women aged 60 years or older attending the Center for the Cohabitation of the Elderly at the Catholic University of Brasília. In order to determine the body composition, we used x - ray Absorptiometry (DXA), InBody 120 and Biodynamics 310e, with and without hydration protocol. Results: Bioimpedance only showed no difference with and without protocol (p = 0.70). Among the age groups there was no difference in fat percentage (p = 0.44) and fat free lean mass (p = 0.22). In the total sample, Bioimpedances underestimate the percentage of body fat and underestimate lean fat free mass compared to DXA. According to nutritional status by the InBody 120, the percentage of fat in the elderly women with low weight, eutrophic and obese were equal to the DXA and fat-free lean mass in obese women. Conclusion: BIA is an instrument capable of measuring body composition in elderly women in front of DXA, but it is necessary to verify the accuracy of the equipment, since both the measurement of the body composition and the performance or not of the hydration protocol will exist differences in the results, independent of the hydration protocol or not.